Value Balance and General Equilibrium Model - Trinh, Truong Hong (International Journal of Economics and Financial Issues, 2017)
This paper proposes a utility function with the incorporation of value and price, and develops a basic general equilibrium model with two conditions of market clearance and value balance. A joint value model is developed to conduct a value balance between firm profit and customer utility that is also a condition for market equilibrium. The simulation experiments are carried out to conduct the value balance between firm profit and customer utility, and the general equilibrium of the economy with economic policies. The study provides key evidence on the value balance between firm profit and customer utility that creates a new paradigm for further researches on partial equilibrium and general equilibrium. Keywords: value concept; utility function; joint value; value balance; general equilibrium JEL Classifications: C61; C68; D46; D50